Transforming Growth Factor-Beta1 in Diabetic Kidney Disease - Zhao, Lijun; Zou, Yutong; Liu, Fang (Frontiers in Cell and Developmental Biology, 2020)
Diabetic kidney disease (DKD) is the leading cause of end-stage renal disease worldwide. Renin-angiotensin-aldosterone system inhibitors and sodium-glucose co-transporter 2 inhibitors have shown efficacy in reducing the risk of end-stage renal disease. However, patients vary in their response to renin-angiotensin-aldosterone system blockades, and the pharmacodynamic responses to sodium-glucose co-transporter 2 inhibitors declines with increasing severity of renal impairment. Thus, effective therapy for DKD is yet unmet. Transforming growth factor-β1 (TGF-β1), expressed by nearly all kidney cell types and infiltrating leukocytes and macrophages, is a pleiotropic cytokine involved in angiogenesis, immunomodulation, and extracellular matrix formation. An overactive TGF-β1 signaling pathway has been implicated as a critical profibrotic factor in the progression of chronic kidney disease in human DKD. In animal studies, TGF-β1 neutralizing antibodies and TGF-β1 signaling inhibitors were effective in ameliorating renal fibrosis in DKD. Conversely, a clinical study of TGF-β1 neutralizing antibodies failed to demonstrate renal efficacy in DKD. However, overexpression of latent TGF-β1 led to anti-inflammatory and anti-fibrosis effects in non-diabetic kidney disease. This evidence implied that complete blocking of TGF-β1 signaling abolished its multiple physiological functions, which are highly associated with undesirable adverse events. Ideal strategies for DKD therapy would be specific and selective inhibition of the profibrotic-related TGF-β1 pathway or blocking conversion of latent TGF-β1 to active TGF-β1.